Organizational functioning in Turkish higher education system: Birnbaum's five models of institutional governance - Hatice Ergin Kocatürk; Engin Karadağ (Journal of Pedagogical Research, 2021)
Expectations from higher education institutions and systems are constantly increasing at both national and global levels. In addition to the variety of services provided by higher education institutions, the rise in expectations makes management of these institutions more difficult. However, while formations such as mission differentiation, thematic university structure, and regional development universities differentiate the objectives of higher education institutions from each other, attempts to achieve these specific objectives may bring along an organizational and informal structure specific to the institution. Based on this premise, the aim of this study is to examine the institution-specific governance models observed in Turkish higher education institutions. This case study is based on the five models of organizational functioning introduced by Birnbaum with the perspective of new institutionalism. The data of the study were obtained from two sources: Existing literature and interviews with 10 academics from higher education institutions. Accordingly, the governance models frequently observed in Turkish higher education institutions are bureaucratic model, political model and organized anarchy. In addition, the rapid increase in the number of higher education institutions and the dependence on resources increase the homogeneity between higher education institutions.